Call for Papers for the joint 186th Meeting of the Acoustical Society of America and the 2024 Acoustics Week in Canada conference - Ghinet, Sebastian; Joana (Canadian Acoustics, 2024)
The joint 186th Meeting of the Acoustical Society of America and the 2024 Acoustics Week in Canada conference will be held from May 13-17, 2024, in downtown Ottawa, Ontario. You are invited to be part of this five days international conference featuring the latest developments in acoustics and vibration. Ottawa is Canada’s capital, a city that reflects the country’s beauty, celebrates its diversity, embodies its spirit, and tells its stories like no other. Located at the confluence of three rivers at the foot of the rugged Canadian shield, Ottawa is home to over one million residents who are proud of their hometown and welcome people in English, French, Indigenous languages, and many more from around the world. The city’s urban landscape reveals Canada around every corner, at historic and national sites, monuments, and cultural institutions. It’s a city that knows how to celebrate, with annual festivals devoted to things near and dear to the hearts of Canadians, including music, arts and the diverse cultural communities that call Ottawa and Canada home. Unique among G7 capitals, Ottawa is equal parts urban and rural, a city on the edge of nature offering boundless opportunities for adventure and recreation in the great outdoors. Put simply, if Canada were a city, Ottawa would be it.